Socio-Psychological Drivers of Livelihood Diversification in Lakshadweep - Anshida Beevi , Monika Wason , R. N. Padaria , N.V. Kumbhare and Eldho Varghese, (Indian Journal of Extension Education, 2015)
Diversification is the incorporation of new activities into the economic portfolio. The rural livelihood diversificationtherefore is an integral dimension of development agenda for strengthening rural livelihood and sustaininglivelihood security. The study was conducted among 120 households in Kalpeni and Andrott islands of U.T. ofLakshadweep to assess the extent of diversification and to analyse the socio-psychological factors promotingdiversification. Respondents were randomly selected and categorized into three livelihood classes based on the share ofagriculture in households' income. Extent of livelihood diversification is studied in terms of number of incomesources of a household and Simpson index of diversification. It is obtained that most of the households were havingdiverse livelihood strategy. It has been found that majority of the diversified households have medium diversificationindex with average diversification index of 0.32. Determinants of diversification were analyzed using Kruskal-Wallistest. It was found out that mass media exposure was the most significant factor leading to diversification followed bysocial participation, change proneness and achievement motivation.